(untitled) (Revista Apotheke, 2025)
This article seeks to reflect on epistolary writing as writing for processes that have characteristics linked to personality in confessional and fictional narratives. The research is based on autobiographical poetic production with letters addressed to reference artists or created personifications. Dialoguing with artists such as Leonilson and Bispo do Rosário and having as a theoretical basis the writings of Leonor Arfuch and Jorge Larrosa on the biographical space and the essay as a mode of writing. The letter, here understood as fiction that performs a dialogue, allows the exploration of affections and divergences in an intimate way and in line with the intentions emotional aspects of the work. Continuous communication, added to the elements that usually constitute correspondence, such as dated records, vocatives, goodbyes and signatures, allow for greater performative and fictional freedom. Experimenting with epistolary writing as an artistic process made it possible to explore the theoretical and affective demands of an essentially intimate production.